KEDUDUKAN, TUGAS POKOK, DAN FUNGSI SERTA EKSISTENSI MAHKAMAH AGUNG DI INDONESIA - Muhammad Faqih (MIMBAR YUSTITIA, 2020)
The Supreme Court is the state institution that exercised the power of the highest judiciary in Indonesia. The power of the judiciary exercised by the Supreme Court is independent, meaning that the Supreme Court is free from the influence or interference of other state powers. As the implementer of Law No. 14 of 1970, formulated the main duties, functions and authorities of the Supreme Court are judicial functions, supervisory functions, administratif functions, and other functions in accordance with the law. The purpose of this research is to find out how the position, basic duties, and functions and existence of the Supreme Court in Indonesia. In this study using legal research that applies four approaches as follows; (1) legal approach; (2) approach problems or matters; (3) comparison and approach; (4) concept approach. A long history records that the existence of the Supreme Court in the Indonesian constitutional system is always contained in the constitution and laws and regulations. The long journey of the Supreme Court made it more concrete and gained the trust of the public related to judicial issues in Indonesia.